Model zatrudnienia terminowego - Ludera-Ruszel, Agata (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The aim and function of definite-term labor contracts in some cases legitimize a deviation from the model determined by indefinite-term employment. Moreover, the aim and function of definite term labor contracts affect the form of definite-term employment relationship. On the basis of the analysis of rules which govern the establishment and termination of employment relationship involving definite-term and trial period employment contracts, the paper is an attempt to present the current model of definite-term employment and its impact on the legal position of the parties to employment relationship
Keywords: praca czasowa; prawo pracy; umowa o pracę na czas określony; zatrudnienie elastyczne